2006
DOI: 10.4141/a06-010
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of parasitological and immunological parameters in sheep with high and low resistance to haemonchosis

Abstract: Correlation of parasitological immunological parameters in sheep with high and low resistance to haemonchosis. Can. J. Anim. Sci. 86: 363-371. Parasitological and immunological parameters of Blackbelly (Bb), a haemonchosis high-resistance sheep breed, and Columbia (Cb) a haemonchosis low-resistance breed were compared. Two experiments were performed: Bb and Cb lambs were infected weekly with 1000 third-stage larvae (L3) of Haemonchus contortus for 6 wk. In the first experiment, faecal egg counts (FEC) and bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…The IgG response was stronger in St. Croix sheep followed by those of Katahdin and Dorper sheep. For IgG, some studies suggest an association between IgG levels and resistance and others relate the IgG production to nematode infection …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IgG response was stronger in St. Croix sheep followed by those of Katahdin and Dorper sheep. For IgG, some studies suggest an association between IgG levels and resistance and others relate the IgG production to nematode infection …”
Section: Discussionmentioning
confidence: 99%
“…Selection for nematode resistance in breeds of sheep and goats has been focused on indicator traits such as FEC . Based on FEC, subtropical and tropical breeds such as St. Croix, Katahdin, Barbados Black Belly, Gulf Coast Native or Santa Ines have been characterized as moderately resistant to H. contortus compared with South African or temperate breeds such as Dorper, Columbia, INRA 401 and Suffolk . However, FEC phenotyping in sheep and goats for selective breeding programmes requires the exposure of the animals to gastrointestinal nematodes, and this has a negative effect on the lifetime production and subsequently will impact the economic status of producers.…”
Section: Introductionmentioning
confidence: 99%
“…The serum antibody response has been widely studied although results have been variable. While some studies show an association between serum IgG levels and resistance [47], others found an association with infection but not with resistance [33, 45]. Abomasum antibodies are more important than serum antibodies in the protection against gastroenteric nematodes.…”
Section: Immune Response In Ovine Haemonchosismentioning
confidence: 99%
“…Thus, both groups respond to the presence of the parasite but do so in different manners. Compared with resistant sheep, susceptible sheep produce relatively more IFN γ and less parasite-specific serum antibodies, blood eosinophils, and abomasum eosinophils [98]; therefore susceptibility is most likely associated with a Th1 type response [47, 50], while resistance includes a Th2 type response. A differential response has also been observed in different abomasum regions.…”
Section: Immune Response In Ovine Haemonchosismentioning
confidence: 99%
“…The larvae 3 (L3) used in the experimental infections were obtained from fecal larval cultures of H. contortusinfected lambs, maintained through successive infections in lambs those were free from gastrointestinal nematodes (Muñoz-Guzmán et al, 2006).…”
Section: Parasitesmentioning
confidence: 99%